Interaksi Hadis dan Budaya Lokal: Living Hadis dalam Tradisi Mattampung Masyarakat Bugis - Aripai, Andi Fatihul Faiz; Amin, Mukhlisah (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2024)
This study examines Mattampung, a traditional death ritual of the Bugis community in Watu Village, Barebbo District, Bone Regency, South Sulawesi. The ritual involves restoring or replacing graves with headstones and is carried out to pray for the deceased. The research is based on the argument that the Mattampung tradition reflects the reception of hadith, particularly those related to the virtues of reciting the Qur’an and offering prayers for the dead, thus shaping the community’s religious practices. This field research adopts a qualitative descriptive approach and was conducted over six months. Primary data were obtained through direct observation, interviews with ten informants, and written and personal documentation. The analysis draws upon the theory of living hadith and Alfred Schutz’s phenomenological framework, which explores human actions through